2000
DOI: 10.1016/s0925-2312(00)00256-3
|View full text |Cite
|
Sign up to set email alerts
|

Unifying cognitive aging: From neuromodulation to representation to cognition

Abstract: An integrative theory relating cognitive aging de"cits observed at the behavioral level with age-related de"ciency in neuromodulation causing less distinctive cortical representations is tested in a series of neural network simulations. Age-related attenuation of catecholaminergic function is simulated by lowering the mean gain of the processing unit, which subsequently reduces responsivity and raises intra-network activation variability. Age di!erences in learning rate, asymptotic performance, interference su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 30 publications
6
78
0
2
Order By: Relevance
“…Our study was guided by the neural noise hypothesis of aging (Welford, 1981(Welford, , 1984 as well as related predictions of greater discriminal dispersion (Allen et al, 1998a(Allen et al, , 1998b, and reduced distinctiveness of neural representations (Li et al, 2000;Li & Sikström, 2002) with advancing adult age. Evidence from animal models (Hua et al, 2006;Liang et al, 2010;Yang et al, 2009) has suggested higher levels of neural noise in the aging nervous system.…”
Section: Rationale and Resultsmentioning
confidence: 99%
“…Our study was guided by the neural noise hypothesis of aging (Welford, 1981(Welford, , 1984 as well as related predictions of greater discriminal dispersion (Allen et al, 1998a(Allen et al, , 1998b, and reduced distinctiveness of neural representations (Li et al, 2000;Li & Sikström, 2002) with advancing adult age. Evidence from animal models (Hua et al, 2006;Liang et al, 2010;Yang et al, 2009) has suggested higher levels of neural noise in the aging nervous system.…”
Section: Rationale and Resultsmentioning
confidence: 99%
“…In an interesting parallel, all the cognitive inefficiencies described earlier have also been found in older adults during normal aging (Braver & Barch, 2002;Daniels et al, 2006;Robbins et al, 1998), and several researchers have explicitly suggested that age-related dopamine depletion is one main contributor to cognitive dysfunction in the elderly (Braver & Barch, 2002;Li et al, 2000;Rubin, 1999). In an earlier study, we assessed the abilities of older and younger adults to perform a complex task involving planning, working memory, and executive control; the task simulated cooking breakfast and was ecologically valid and interesting to carry out (Craik & Bialystok, 2006).…”
Section: Introductionmentioning
confidence: 80%
“…A recent life span study (Li et al, 2004) demonstrated that trial-to-trial variability becomes increasingly predictive of fluid intelligence in older age. Such increased trial-to-trial variability in aging may represent the effects of degraded neural processing efficiency associated with neurological disease (Hultsch, MacDonald, Hunter, Levy-Bencheton, & Strauss, 2000) or the aging brain (Li, Lindenberger, & Frensch, 2000). Salthouse and Berish (2005) identified several reasons why understanding the causes and correlates of WP variability is important on both practical and theoretical grounds.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%